Cultural rights : technology, legality, and personality - Lury, Celia (International library of sociology., 1993)
This astute and timely book investigates the radical potential of technically unlimited reproduction in postmodern culture. It describes a move towards a regime of cultural rights ordered by simulation rather than originality.